Effects of Drugs: Anti-Punishment and Anti-Conflict Procedures - Rasmussen, Erin B. (Mexican Journal of Behavior Analysis, 2011)
Anxiolytic drugs are said to reduce internal states (e.g., anxiety) that are induced by the presentation of aversive events, leading to a release of behavior that has been suppressed. The objective of the present paper is to discuss two categories of procedures that are often used interchangeably– anti-punishment (procedures that release punished behavior) and anti-confl ict (procedures that reduce avoidance behavior). Similarities and differences between the two categories of procedures are reviewed, emphasizing distinctions between theoretical, methodological, and pharmacological specifi cs. The anxiety-as-explanation issue is discussed also, in terms of possibly obscuring the behavioral and pharmacological mechanisms that are involved with drugs that “release” behavior.